Media framing of the free Malaysia today and the star english language online news portal: The case studies of Malaysia’s 15th general election 2022 - Ng Wei Liang; Lee Kuok Tiung (Human Resource Management Academic Research Society (HRMARS), 2024)
This study examines the framing techniques employed by the English language online news portals, namely Free Malaysia Today and The Star, in their coverage of the Malaysia 15th General Election (GE-15). The objective is to conduct a comparative content analysis of how these news portals framed the news during the GE-15. The study employs a quantitative research approach, utilizing content analysis as the primary method of data collection and analysis. A total of 418 news (N=418) articles related to the GE-15 from both Free Malaysia Today and The Star have systematically selected and analysed within a specific timeframe (5/11/2022-19/5/2022) to identify the framing strategies utilized in their coverage. The findings of this study contribute to the existing body of knowledge on news framing and media representation of elections in Malaysia. Through the comparative content analysis, findings reveal that two different news portals have dominant frames and present political news differently, having problems on potential biases, perspectives, and their impact on public opinion. The frequency of occurrence of these framing strategies in the news articles have assessed their similarities and differences. Particularly during the GE-15, the articles in both media platforms primarily aimed at reinforcing their respective ideological stances rather than offering alternative explanations or dissenting views.